NATURAL MODELING OF GALACTIC AND EXTRAGALACTIC STRUCTURES - Shatsova, R. B.; Anisimova, G. B. (Одеські астрономічні публікації, 2017)
The Universal Sky Net (USN) is proposed. Its elements correspond to the details of different scale structures. The examples of modeling by means of USN are cited for the system of globular clusters, for the galaxies of Local group and for the galaxies of two superclusters.